Influence of the Extraction Location on the Physical and Mechanical Properties of the Pseudo-Trunk Banana Fibers. Issue 2 (18th August 2023) - Libog, Laurent; Biyeme, Florent; Betené, Achille Désiré Omgba; Biwolé, Achille Bernard; Ndiwe, Benoit; Mbang, Jonas Peequeur Essome; Claude, Takoumbe; Mbey, Jean Aimé; Meva'a, Jean Raymond Lucien
ABSTRACT: The specific properties and availability of banana pseudo-trunk fibers make them a promising alternative for the development of green composites. However, the wide dispersion of their properties can hinder their use. In this study, the influence of the sampling area of the banana pseudo-trunk on the physical and mechanical properties of the fibers was evaluated. Prior to retting, the trunk was sampled longitudinally (bottom, middle and top) and transversely (periphery, intermediate and heart). Gravimetric tests were carried out and revealed variations in water absorption (347.1–517.4%), density (0.92–1.45 g.cm −3 ) and linear mass (25 -34tex). Tensile tests were also performed and showed a significant effect of fiber location on Young's modulus (6.60–34.6GPa), tensile strength (91-350MPa) and elongation at the break (0.9–2.6%). Due to diameter scatter, variations of 42% were found for fibers in the same area. In a region, the physical properties increase from the periphery to the core, and the mechanical properties decrease in the same direction, except for elongation. The results of this study showed good agreement with those of other natural fiber types. However, we recommend the peripheral areas of the pseudo-trunk to extract reinforcing fibers from composites because of their low density (0.9 g.cm −3 ) and their high stiffness (34GPa).